2020
DOI: 10.7759/cureus.12296
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an In Vitro Fertilization Pregnancy With COVID-19 and the Perinatal Outcome in Riyadh, Saudi Arabia

Abstract: Coronavirus disease 2019 caused by the novel severe respiratory syndrome coronavirus 2 (SARS-CoV-2) is a pandemic and potentially fatal disease. COVID-19 cases are on the rise globally; this also includes risk groups such as pregnant women and neonates. Herein, we report the first COVID-19 cesarean delivery case of an in vitro fertilization (IVF) pregnancy in a Saudi woman. A postdate pregnant healthy woman tested positive with COVID-19 on her 38 weeks + five days. On her 40 weeks + five days, the woman had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The low mortality rate and ICU admission reported from Iran and KSA are similar to the one observed in several studies worldwide conducted on pregnant women infected with SARS-CoV-2 ( Allotey et al, 2020 ; Elshafeey et al, 2020 ; Juan et al, 2020 ; Smith et al, 2020 ). In pregnant women with COVID-19 in this country, vaginal delivery was more prevalent than the cesarian one ( Algadeeb et al, 2020 ; Alhamoud et al, 2020 ; Al-Matary et al, 2021 ; AlQurashi et al, 2021 ). The most frequent adverse pregnancy outcomes were premature followed by fetal distress, and preeclampsia which occurred in pregnant women <37 weeks of gestational age ( Al-Matary et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 88%
See 1 more Smart Citation
“…The low mortality rate and ICU admission reported from Iran and KSA are similar to the one observed in several studies worldwide conducted on pregnant women infected with SARS-CoV-2 ( Allotey et al, 2020 ; Elshafeey et al, 2020 ; Juan et al, 2020 ; Smith et al, 2020 ). In pregnant women with COVID-19 in this country, vaginal delivery was more prevalent than the cesarian one ( Algadeeb et al, 2020 ; Alhamoud et al, 2020 ; Al-Matary et al, 2021 ; AlQurashi et al, 2021 ). The most frequent adverse pregnancy outcomes were premature followed by fetal distress, and preeclampsia which occurred in pregnant women <37 weeks of gestational age ( Al-Matary et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 88%
“…One study found that the most common symptoms were cough, fever, and dyspnea ( Al-Matary et al, 2021 ). The majority of infected pregnant women did not have comorbidities and experienced a mild or moderate disease ( Alhamoud et al, 2020 ; Al-Matary et al, 2021 ; AlQurashi et al, 2021 ). A small proportion only, required intensive care and respiratory support as they developed symptoms of pneumonia; this finding was reported in pregnant women between 26 and 36 weeks of gestational age ( Al-Matary et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%